Characterization and photocatalytic activity of nanoparticulate GdMnO3 prepared by sol-gel method. (10th December 2017) - Sun, Dandan; Xie, Xinyu; Tang, Peisong; Xu, Yunyi; Chen, Haifeng; Yu, Longlong; Yang, Jiani
ABSTRACT: The GdMnO3 was prepared using gadolinium nitrate (III) hexahydrate, manganese acetate and citric acid by a facile sol-gel method. The gel of GdMnO3 was kept at 100°C for 24 h to get the xerogel. Then, the xerogel was respectively calcined in muffle furnace at 700°C, 800°C, 900°C and 1000°C to make single phase nanoparticulate GdMnO3 . The prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) spectroscopy. The photocatalytic activities of GdMnO3 were investigated by methyl orange which was used as simulated sewage. The results show that the pure GdMnO3 can be obtained through calcination at 800°C, and the GdMnO3 have an average particle size of 80–100 nm. The photocatalytic experiment demonstrates that GdMnO3 is highly photocatalytic active for the degradation of methyl orange under ultraviolet light irradiation.